Detectability of fiducials' positions for real‐time target tracking system equipping with a standard linac for multiple fiducial markers. Issue 11 (15th October 2020) - Ono, Shunsuke; Ueda, Yoshihiro; Ohira, Shingo; Isono, Masaru; Sumida, Iori; Inui, Shoki; Morimoto, Masahiro; Ashida, Reiko; Miyazaki, Masayoshi; Ogawa, Kazuhiko; Teshima, Teruki
Abstract: Purpose: To investigate the detectability of fiducial markers' positions for real‐time target tracking system equipping with a standard linac. The hypothesis is that the detectability depends on the type of fiducial marker and the gantry angle of acquired triggered images. Methods: Three types of ball fiducials and four slim fiducials with lengths of 3 and 5 mm were prepared for this study. Triggered images with three similar fiducials were acquired at every 10° during the conformal arc irradiation to detect the target position. Although only one type of arrangement was prepared for the ball fiducials, a three‐type arrangement was prepared for the slim fiducials, such as parallel, orthogonal, and oblique with 45° to the gantry‐couch direction. To measure the detectability of the real‐time target tracking system for each fiducial and arrangement, detected marker positions were compared with expected marker positions at every angle of acquired triggered images. Results: For the ball‐ type fiducial, the maximum difference between the detected marker positions and expected marker positions was 0.3 mm in all directions. For the slim fiducial arranged parallel and oblique with 45°, the maximum difference was 0.4 mm in all directions. When each slim fiducial was arranged orthogonal to the gantry‐couch direction, the maximum difference was 1.5 mm for the length of 3 mm, and 3.2 mm for the length of 5 mm. Conclusions: The detectability of fiducial markers' positions for the real‐time target tracking system equipping with a standard linac depends on the form and insertion angles of the fiducials.